Capsaicin as a Therapeutic Molecule 2014
DOI: 10.1007/978-3-0348-0828-6_8
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Antitumor Effects of Capsaicin

Abstract: Capsaicin, one of the major pungent ingredients found in red peppers, has been recently demonstrated to induce apoptosis in many types of malignant cell lines including colon adenocarcinoma, pancreatic cancer, hepatocellular carcinoma, prostate cancer, breast cancer, and many others. The mechanism whereby capsaicin induces apoptosis in cancer cells is not completely elucidated but involves intracellular calcium increase, reactive oxygen species generation, disruption of mitochondrial membrane transition potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 113 publications
1
51
0
1
Order By: Relevance
“…Capsaicin was reported to bind to the transient receptor potential vanilloid (TRPV1) receptor, leading to desensitization of peripheral nerves to noxious stimuli 11 . Numerous recent research reports have convincingly shown that capsaicin induces cell cycle arrest and apoptotic cancer cell death in a variety of cancer cell lines including colon adenocarcinoma, pancreatic cancer, hepatocellular carcinoma, prostate cancer, breast cancer, and many others 12 . Interestingly, many of the pathways inhibited by capsaicin treatment involve Hsp90 client proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Capsaicin was reported to bind to the transient receptor potential vanilloid (TRPV1) receptor, leading to desensitization of peripheral nerves to noxious stimuli 11 . Numerous recent research reports have convincingly shown that capsaicin induces cell cycle arrest and apoptotic cancer cell death in a variety of cancer cell lines including colon adenocarcinoma, pancreatic cancer, hepatocellular carcinoma, prostate cancer, breast cancer, and many others 12 . Interestingly, many of the pathways inhibited by capsaicin treatment involve Hsp90 client proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortuntely, although tumor cells express higher levels of TRPV1 than normal epithelial cells, they still do not have enough receptors to perform tumor-targeted TRPV1-mediated necrotic-type eradication (Pecze et al, 2016b). Nevertheless, several experiments (Diaz-Laviada and Rodriguez-Henche, 2014) as well as a case report (Jankovic et al, 2010) suggest that vanilloids have anti-cancer activity. The origin of the anticancer effects of vanilloids is not completely solved and it needs further examination.…”
Section: Safety and Efficacy Of Molecular Surgery Agents In Humansmentioning
confidence: 99%
“…The origin of the anticancer effects of vanilloids is not completely solved and it needs further examination. Whether it is TRPV1-mediated or a TRPV1-independent effect is still in question (Diaz-Laviada and Rodriguez-Henche, 2014). To make things more complicated, pain sensing neurons innervate the tumor mass and communicate with the tumors (Li et al, 2013).…”
Section: Safety and Efficacy Of Molecular Surgery Agents In Humansmentioning
confidence: 99%
“…Accumulated evidence has also demonstrated that capsaicinoid has potential beneficial effect on the human cardiovascular system [14,15,16]. It has also been reported that capsaicinoid possesses antitumor activity [17,18]. Capsaicinoids have been shown to possess antioxidant activity with an ability to prevent excessive formation of ROS (reactive oxygen species) [19,20] There are few reports on the antioxidant activity of capsaicin [21,22].…”
Section: Introductionmentioning
confidence: 99%